Change in genotype of methicillin-resistant Staphylococcus aureus (MRSA) affects the antibiogram of hospital-acquired MRSA. Issue 7 (July 2018) - Harada, Dai; Nakaminami, Hidemasa; Miyajima, Eri; Sugiyama, Taku; Sasai, Nao; Kitamura, Yoshinobu; Tamura, Taku; Kawakubo, Takashi; Noguchi, Norihisa
Abstract: Recently, the dissemination of community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) into hospitals has frequently been reported worldwide. Hospital-acquired MRSA (HA-MRSA) strains exhibit high-level resistance to multiple antimicrobial agents, whereas CA-MRSA strains are usually susceptible to non-β-lactams. Thus, it is predicted that the antibiogram of the HA-MRSA population would change along with the change in genotype of MRSA. Here, we investigated the changes in the MRSA population along with the MRSA antibiogram in a hospital between 2010 and 2016. Staphylococcal cassette chromosome (SCC) mec typing showed that the predominant HA-MRSA strains in the hospital dramatically changed from SCC mec type II, which is the major type of HA-MRSA, to SCC mec type IV, which is the major type of CA-MRSA. Multilocus sequence typing revealed that the predominant SCC mec type IV strain was a clonal complex (CC) 8 clone, which is mainly found among CA-MRSA. Furthermore, the CC1-SCC mec type IV (CC1-IV) clone significantly increased. Both the CC8-IV and CC1-IV clones exhibited high antimicrobial susceptibility. The antibiogram change of the HA-MRSA population was consistent with the antimicrobial susceptibilities and increased prevalence of the CC8-IV and CC1-IV clones. Our data reveal that the change in the genotypes of MRSA strains could impact the antibiogram of HA-MRSA population.